SYNTHESIS OF SURFACTANS DILAUROYL MALTOSE THROUGH ACETILATION REACTION OF MALTOSE FOLLOWED BY TRANSESTERIFICATION REACTION WITH METHYL LAURATE - Daniel Tarigan (Indonesian Journal of Chemistry, 2009)
Maltose has been partially acetylated from the reaction of melted maltose and acetic anhydride without solvent and catalyst to produce maltocyl acetate with the yield of 67%. Lauryc acid can be methanolized using H2SO4 as the catalyst to produce methyl laurate with the yield of 92%. The transesterification of methyl laurate and maltocyl acetate in methanol using sodium methoxyde as the catalyst at reflux, yielded a novel compound dilauroyl maltose after isolated by column chromatography, with the yield of 59%. Methyl laurate, maltocyl acetate, and dilauroyl maltose were confirmed by FT-IR and 'H-NMR spectroscopy, and the surface tension of dilauroyl maltose solution  was determined by Du-Nuoy tensiometer to obtain the HLB value of 2.67.